Advances in 2D/3D Printing of Functional Nanomaterials and Their Applications - Choi, Jea-Young; Das, Sayantan; Theodore, N. David; Kim, Inho; Honsberg, Christiana; Choi, Hyung Woo; Alford, T. L. (ELECTROCHEMICAL SOC INC, 2015)
Advanced printing techniques include innovative and/or integrated processes that are used to produce an object with enhanced functionality and with a wide range of applications. This is done by realizing printing of functional materials such as ink, paste, polymer, ceramic powder, and organic materials. Unlike conventional manufacturing methods, a new technique is needed to manipulate small objects to fabricate desired parts, as materials are scaled down to the nanometer range. In this regard, the traditional subtractive production has been changed to a bottom-up approach as device structures have changed to multilayer structures which contain several functional nanomaterials. A powder is used to fabricate an object with a desired geometry. This reduces the material loss due to the bottom-up nature of the process. In this article, we review the current state of knowledge for advanced manufacturing using two methods, 3D printing and roll-to-roll manufacturing. Several applications of 3D printing and nanotechnological development are also being considered here. (C) The Author(s) 2015. Published by ECS. All rights reserved.
Keywords: TO-ROLL FABRICATION; CALCIUM-PHOSPHATE; PHOTOVOLTAIC DEVICES; HUMIDITY SENSORS; TISSUE; BONE; ELECTRODES; SCAFFOLDS; COLLAGEN; DESIGN